2014
DOI: 10.1021/ic5004484
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermodynamic Study of the Complexes of Nd(III) with N,N,N′,N′-Tetramethyl-3-oxa-glutaramide and the Acid Analogues

Abstract: The thermodynamics of Nd(III) complexes with N,N,N',N'-tetramethyl-3-oxa-glutaramide (TMOGA, L(I)), N,N-dimethyl-3-oxa-glutaramic acid (DMOGA, HL(II)), and oxydiacetic acid (ODA, H2L(III)) in aqueous solutions was studied. Stability constants, enthalpies, and entropies of complexation were determined by spectrophotometry, potentiometry, and calorimetry. The stability constants of corresponding Nd(III) complexes decrease in the following order: Nd(III)/L(III) > Nd(III)/L(II) > Nd(III)/L(I). For all complexes, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 35 publications
7
58
0
Order By: Relevance
“…Recently, a similar geometry of the RE-DGAA complex was reported by Tian et al in their studies on the Nd-DGAA complex prepared by N,N-dimethyldiglycolamic acid with a tertiary amide group [26].…”
Section: Slope Analysis and Structure Of La-dgaa Complexsupporting
confidence: 70%
“…Recently, a similar geometry of the RE-DGAA complex was reported by Tian et al in their studies on the Nd-DGAA complex prepared by N,N-dimethyldiglycolamic acid with a tertiary amide group [26].…”
Section: Slope Analysis and Structure Of La-dgaa Complexsupporting
confidence: 70%
“…3–4 mmol/L to which a calculated aliquot of the titrant (ligand solution in C 8 mim · Tf 2 N) was added. Similar titrations at macroconcentration of Nd 3+ with water soluble DGA ligands have been performed earlier with large stability constant values . The stability constant data were further verified by the potentiometric titration suggesting that the absorption spectroscopy technique can be used for obtaining complex formation data having large stability constant values.…”
Section: Methodssupporting
confidence: 73%
“…To help understand the thermodynamic and structural properties of the actinide complexes with DGA ligands, a number of studies have been conducted in recent years by using small alkyl groups (e.g., methyl) to render the DGA ligands watersoluble so that a variety of techniques, such as potentiometry, spectrophotometry, and calorimetry, are applicable to the studies. [12,13,14,15] The alkyl-substituted DGA ligands are usually tridentate to the metal ions, using the two amide oxygen atoms and the center ether oxygen. 4 [12,13,14,15] Considering that no substitutional groups can be attached to the ether oxygen of DGA to vary the basicity and binding strength of the ligands, we have previously synthesized and conducted the studies of a series of structurally related amine-bridged diacetamide ligands, including…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that these ligands form stronger complexes with Nd 3+ , [16] UO 2 2+ , [17] or NpO 2 + , [18] than TMDGA. [12,13,15] In a tridentate mode similar to the DGA ligands, the amine-bridged diacetamides coordinate to the metal ions via the two amide oxygen atoms and the central nitrogen.…”
Section: Introductionmentioning
confidence: 99%